2018
DOI: 10.1111/jar.12549
|View full text |Cite
|
Sign up to set email alerts
|

Trauma exposure and post‐traumatic stress disorder in people with intellectual disabilities: A Delphi expert rating

Abstract: Background There is a lack of research on trauma in people with intellectual disabilities. This study assessed expert consensus on the traumatic potential of a broader range of adverse life events, and differences in symptom manifestation and behavioural symptom equivalents of post‐traumatic stress disorder (PTSD) symptoms. Method The present authors conducted a three‐step Delphi survey using a mixed‐methods design. Twenty‐nine expert raters participated in the survey, and 16 persisted to the final round. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Trauma‐related symptoms were described following events that would rarely be considered traumatic in the general population, suggesting that a broader range of events need to be considered when assessing PTSD and trauma‐related symptoms in individuals with ASD and ID. This is in line with previous suggestions that ASD increases vulnerability to PTSD (Brewin et al, 2019; Kerns et al, 2015; Peterson et al, 2019; Rumball, 2019) and that individuals with ID may develop PTSD following less severe events than those included in the DSM 5 criterion A (American Psychiatric Association, 2013; McCarthy et al, 2017; Rittmannsberger et al, 2019). Examples provided by the informants suggest that this may be due to, for instance, sensory processing issues (Brewin et al, 2019), or because individuals lack access to information others take for granted.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Trauma‐related symptoms were described following events that would rarely be considered traumatic in the general population, suggesting that a broader range of events need to be considered when assessing PTSD and trauma‐related symptoms in individuals with ASD and ID. This is in line with previous suggestions that ASD increases vulnerability to PTSD (Brewin et al, 2019; Kerns et al, 2015; Peterson et al, 2019; Rumball, 2019) and that individuals with ID may develop PTSD following less severe events than those included in the DSM 5 criterion A (American Psychiatric Association, 2013; McCarthy et al, 2017; Rittmannsberger et al, 2019). Examples provided by the informants suggest that this may be due to, for instance, sensory processing issues (Brewin et al, 2019), or because individuals lack access to information others take for granted.…”
Section: Discussionsupporting
confidence: 87%
“…Expression of psychiatric disorder in general may be affected by both ASD and ID (Bakken et al, 2016; Helverschou et al, 2011), and assessments may rely on clinicians' or caregivers' recognition of behavioural expressions of psychiatric symptoms, particularly in individuals with more severe levels of ID (Fletcher, Barnhill, & Cooper, 2017). While current knowledge regarding behavioural expressions of PTSD symptoms in individuals with ASD and ID is limited (Kildahl et al, 2019; Rittmannsberger, Kocman, Weber, & Lueger‐Schuster, 2019), it has been suggested that presentation of PTSD in more severe levels of ID may align with symptom presentation in typically developing children (McCarthy, 2001; Mevissen, Didden, & de Jongh, 2016), including behavioural acting out of traumatic experiences and increased likelihood of disorganized or agitated behaviours (McCarthy et al, 2017). Moreover, individuals with ASD may display symptoms of psychiatric disorder in idiosyncratic or atypical ways, such as changes to the quality, frequency or intensity of repetitive behaviours (Rosen, Mazefsky, Vasa, & Lerner, 2018), but knowledge is sparse with regards to PTSD (Kildahl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge regarding individuals' trauma experiences and interpretation of behavior were seen as important to identify the more PTSDspecific symptoms reexperiencing and avoidance, underlining the need for psychiatric assessment in this population to be trauma sensitive, thorough, and multi-dimensional. Challenges recognizing and identifying reexperiencing and avoidance in individuals with ASD and ID have previously been suggested to relate to these symptoms' intra-psychic nature and patients' lack of verbal abilities (Kildahl et al, 2019;Rittmannsberger et al, 2019). Current findings indicate that this may only be a partial explanation, as development of reexperiencing and avoidance may follow different trajectories in some individuals with ASD and ID and thus be expressed in a wider range of ways.…”
Section: Discussionmentioning
confidence: 70%
“…Behavioural symptoms may occur as an expression of or reaction to intrusion symptoms, or as a response to an inability to avoid triggers due to a lack of autonomy (Wigham & Emerson, 2015). People with intellectual disabilities might lack the skills to understand these symptoms and therefore have trouble verbalizing them or recognizing them from an interviewer's description (Rittmannsberger et al, 2019). The current possibilities for verbal self‐report assessment seem to be insufficient to gain adequate insight into these symptoms in people with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this claim is supported by previous studies literature: experienced professionals and practitioners suggest that events going beyond the definition of the gate criterion, such as parental bereavement and having children removed, were common sources of trauma (Mitchell & Clegg, 2005). Moreover, expert raters considered such events as potentially traumatic for people with intellectual disabilities, especially events revolving around the broader themes of sexuality and autonomy (Rittmannsberger, Kocman, Weber, & Lueger‐Schuster, 2019).…”
Section: Introductionmentioning
confidence: 99%